Monitoring the Transition from Spherical to Polymer‐like Surfactant Micelles Using Small‐Angle X‐Ray Scattering1. (4th September 2014) - Jensen, Grethe Vestergaard; Lund, Reidar; Gummel, Jérémie; Narayanan, Theyencheri; Pedersen, Jan Skov
Abstract Despite over a century of modern surfactant science, the kinetic pathways of morphological transitions in micellar systems are still not well understood. This is mainly as a result of the lack of sufficiently fast methods that can capture the structural changes of such transitions. Herein, a simple surfactant system consisting of sodium dodecyl sulfate (SDS) in aqueous NaCl solutions is investigated. Combining synchrotron radiation small‐angle X‐ray scattering (SAXS) with fast stopped‐flow mixing schemes allows monitoring the process where polymer‐like micelles are formed from globular micelles when the salt concentration is suddenly increased. The results show that "worm‐like" micelles are formed by fusion of globular micelles and short cylinders in a fashion that bears similarities to a step‐like polymerization process.